Pengaruh Inflasi Suku Bunga dan Nilai Tukar Rupiah Terhadap Harga Saham Perusahaan Di Sektor Manufaktur Yang Terdaftar di Bursa Efek Indonesia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to determine inflation tests, interest rates, exchange rates on share prices in companies in the manufacture sector listed on the Indonesia Stock Exchange. The research method used is a quantitative method using the Statistical Package For The Social Sciences (SPSS) to measure the results of Inflation, Interest Rates, Rupiah Exchange Rates on Stock Prices. This research uses a sampling technique, namely a porprosive sampling with 20 companies that have certain criteria. The results of this study show that inflation has no significant effect on stock prices, interest rates have no significant effect on stock prices, and exchange rates have a significant effect on stock prices.
Keywords: Inflation, Interest Rates, Rupiah Exchange Rate, Stock Prices